Effect of fluoxetine and a low-carbohydrate diet on cardiometabolic risk markers in subjects at risk of diabetes mellitus - Gordillo-Cortaza, Janet Del R; Pozo-Verdesoto, Socrates D; Sanclemente-Lainez, Gisella K; Viteri-Gomez, Giomar R; Gomez-Rutti, Yuliana Y; Feraud-Ibarra, Fatima V; Vasquez- Rodriguez, Nancy A; Gonzalez-Garcia, Walter A; Poveda-Navarrete, Shirley (Revista Universidad de Guayaquil, 2021)
Background: Low carbohydrate diets are a good strategy to reduce weight, regulate insulin levels and anthropometric parameters in obese patients with an adverse cardiovascular profile. Objective: To determine the effect of fluoxetine, with a low carbohydrate diet in subjects at risk of diabetes mellitus. Materials and Methods: An observational and retrospective study was carried out, 162 medical records of the Nutrition Service at the University Hospital Guayaquil, were reviewed. 81 patients who followed a low carbohydrate diet
Keywords: Fluoxetine; Diet; Mellitus Diabetes